Conserved homeodomain cysteines confer redox sensitivity and influence the DNA binding properties of plant class III HD-Zip proteins - Comelli, Raul Nicolas (2007)
The role of four cysteines present within the homeodomain of the homeodomain-leucine zipper (HD-Zip) class III protein Athb-9 has been studied. DNA binding by the Athb-9 HD-Zip domain was only observed after incubation in the presence of reducing agents or the thioredoxin system, suggesting that the protein is sensitive to redox conditions. A similar behavior was observed for proteins that show the same binding specificity of Athb-9 present in nuclear extracts. The use of single and double mutants indicated that two out of three of the cysteines at positions 23, 38 and 42 are required for redox sensitivity, while Cys58 is not involved. A role of Cys23 and Cys58 in determining the DNA binding efficiency and specificity, respectively, of the reduced Athb-9 HD-Zip domain was also evident from these studies. It can be postulated that redox conditions may modulate the function of Athb-9 in plant development. Sequence conservation suggests that the results can be extended to all HD-Zip III transcription factors.